Enterotoxigenic potential and molecular typing of Staphylococcus sp. isolated from organic and conventional fresh minas cheese in the state of São Paulo, Brazil - da Silva Cândido, Talita Junia; da Silva, Anderson Clayton; de Matos, Luiz Gustavo; da Silva do Nascimento, Maristela; Camargo, Carlos Henrique; Cobo Zanella, Rosemeire; Mores Rall, Vera Lúcia [UNESP]; Cirone Silva, Nathália Cristina (Elsevier, 2020)
The aim of this study was to isolate, identify and perform molecular characterisation of Staphylococcus sp. isolated from the processing chain of organic and conventional fresh Minas cheese. The most common enterotoxin encoding gene observed among the isolates was seg (35.8% of isolates) and sei (21.1%). No difference was observed between samples from organic and conventional dairies, and between cheeses. agr type III was the most commonly found (44.8%), followed by type II (29%) and type I (13.2%). Fourteen different spa types were identified. PFGE showed 17 different clusters; 5 clusters presented 2 clones with 100% similarity. Results obtained from the PFGE, paired with spa typing and agr typing, support the identification of the main transmission points of Staphylococcus aureus strains as being the brine process, tools (lyre slicer), and raw and pasteurised milk used for producing fresh Minas cheese.